Epidemiology of hydatid disease in the department Maracó in the Province of La Pampa (Veterinary Science, 2017)
The Echinococcus granulosus is the agent that causes the classical hydatidosis or cystic echinococcosis. The most enlarged cycle in South America is the sheep-dog cycle, it offers excellent conditions for the development of the parasite. The province of La Pampa shows an endemic presence with notification of human cases and infected dogs. The distribution and prevalence of the disease in the Department of Maracó, La Pampa , Argentina was evaluated during the years 1996 and 1997.Dogs of 36 fanns that had ovines, were dosed with arecoline hydrobromide at doses of 3.5 mg/kg , the result obtained was that 75% were positive to Tennia spp. and 8% to Echinococcus granulosus. In total 137 dogs were evaluated , being from 3 to 4 per fann, from wich 58% were positive to Tennia spp. and 2,6% to Echinococcus granulosus. Infonnation from 187.790 slaughtered cattle was obtained between the years 1996 and 1997 in two slaughterhouses in the province of La Pampa. Analysis from the clinical records indicated 11 human cases that appeared during the period 96/97 (annual incidence rate of 6.79 x 100.000 inhabitants). As a concequence, it is of sanitary nterest to enlarge the investigations in other districts of the province of La Pampa with the aim of delimiting the endemic distribution area within the province, and also organising epidemiologic watchfulness systems of the illnes
Keywords: Echinococcus granulosus; Hydatidosis